"Nailable" External Fixation of the Tibia: A Novel Technique to Accommodate Delayed Intramedullary Nailing of the Tibia. Issue 11 (November 2020) - Savage-Elliott, Ian; Wu, Victor J.; Nguyen, Lan N.; Martin, Murphy P.; Gladden, Paul B.
Abstract : Summary: External fixation is often used for temporary stabilization of the tibia in several clinical scenarios. Conventional placement of external fixation pins may impede instrumentation with intramedullary nailing, thus requiring pin removal, loss of reduction, and increased operative time during definite fixation. In this article, we describe a strategic pin placement routinely used at our institution in which we create a medially based inverted triangular construct that allows for pins to remain in place during definitive fixation. Abstract : Supplemental Digital Content is Available in the Text.